TRAINING FOR LAW AND PUBLIC ACCOUNTING. - Campfield, William L. (The Accounting Review, 1953)
A profession is characterized by the type of activity in which its members are required to possess a highly specialized knowledge and have the ability to apply it with skill and wisdom in the rendition of personal service. That a philosophical bent pervades modem thinking about the implementation of the methodology of each of the two professions, Law and Public Accounting, is evident to any reasonably informed person. This trend implies the existence and need of a dose interrelation and interdependence between the two professions. In the professional curricula for each of the subject fields there has been a tendency to supplement the basic offerings of theory with well chosen cases carefully integrated with the theory. With respect to coordinated training programs by organized practitioners and cooperating colleges and universities, the two professions are highly comparable. Each has a strong national society supported by well organized and integrated state societies or associations. The majority of practitioners in each profession will hold membership in either or both of the types of societies operating in the respective fields. It is to be noted in connection with the above comparison that a few states have, in recent years, been requiring or experimenting with short internship or probationary practice periods as requisites to final licensing for legal practice. It may be concluded that the training programs for each of highly specialized professions such as Law and Public Accounting tend to turn out products who possess trained abilities to render opinions and decisions that are free from illusion or personal desire, but instead are founded upon intellect and reason.